Innovative Approaches to Non-Standard Forms of Employment: Experience of Volunteers Recruiting - Galyna KRAPIVINA; Larysa NOVAK-KALYAYEVA; Iryna SURINA; Iryna SHAPOVALOVA; Agata WOZNIAK-KRAKOWIAN (Communications of International Proceedings, 2021)
The article, based on the study of the world literary heritage, shows an analysis of innovative approaches to non-standard forms of employment on the example of the experience of public administration in the use of non-standard forms of employment, volunteering. On the example of the world Olympic movement, the history of the development of the use of non-standard forms of employment by state bodies, volunteering in the service of large sports competitions, is shown. Particular attention in the article is paid to the social significance, organizational aspects and peculiarities of the use of volunteers by state bodies of the participating countries and cities - the organizers of the Olympics. A study of the key aspects of the process of attracting precarious forms of volunteering by government bodies to the Olympic Games showed that government bodies began using Olympic volunteers as early as 1896 during the First Games in Athens. Officially, volunteers began to participate in the organization and conduct of the Olympic Games more than 10 years later. The importance of the non-standard form of employment, volunteering, for the success of the Olympic Games was officially announced by the state administration bodies only in 1980. It is shown that the state bodies of the cities - the organizers of the Olympic Games carefully determine innovative approaches to the use of attracted paid personnel and invited volunteers, as well as the main directions of use and functions of non-standard forms of employment volunteering. The article shows that innovative approaches of public administration to service maintenance of large sports competitions with the involvement of non-standard forms of employment, volunteering, significantly reduce the cost of holding the Olympics and reduce the contribution of the participating countries to them.
Keywords: Public Administration; Employment; Non-Standard Form Of Employment Volunteering; Large Sports Competitions; Volunteers.